THE INTERACTION OF EXTRAVERSION AND NEUROTICISM IN PREDICTING SELF-IDENTITY CRISIS AMONG ADOLESCENTS IN SOUTHEAST NIGERIA: THE MODERATING ROLE OF SOCIAL SUPPORT - Ihekeremma Onuoha, Florence; Okechukwu Okafor, Chiedozie; Andrew Onwuegbuchulam, Chijioke (African Journal of Social and Behavioural Sciences, 2024)
This study investigated extraversion, neuroticism, and social support as predictors of adolescent identity crisis, guided by Erikson’s (1968) identity development theory. Erikson’s model highlights adolescence as a critical phase for resolving identity versus role confusion, where personal traits and external support shape self-perception. The participants included 216 high school seniors aged 14 to 19 (M = 16.94) from 12 Community Secondary Schools in southeastern Nigeria. Five hypotheses were tested, with a focus on whether extraversion, neuroticism, and social support predict identity crises. Hypothesis 1 posited that extraversion would not significantly predict identity crisis, whereas Hypothesis 3 suggested that social support would be a strong predictor. Hypothesis 4 proposed that social support would moderate the relationship between extraversion and identity crisis. Using the Self-Identity Crisis Questionnaire (SICQ), the Big Five Personality Inventory, and the multidimensional Scale of Perceived Social Support (MSPSS), the results revealed that extraversion (b = .11, t = 1.49, p = .136) and neuroticism (b = .11, t = 1.57, p = .117) did not predict identity crises. However, social support significantly predicted identity crisis (b = .11, t = 1.49, p = .136). Social support did not moderate the extraversion–identity crisis relationship (b = .01, t = 1.184, p = .23), but it did moderate the effect of neuroticism. In line with Erikson’s theory, the findings emphasize the crucial role of social support in adolescent identity formation. This suggests that fostering supportive environments can reduce identity crises, especially for adolescents with neurotic tendencies, helping them navigate this critical developmental stage.